Implications of m6A methylation and microbiota interaction in non-small cell lung cancer: From basics to therapeutics - Qiu, Fen-Sheng; He, Jia-Qi; Zhong, Yu-Sen; Guo, Mei-Ying; Yu, Chen-Huan (Frontiers in Cellular and Infection Microbiology, 2022)
N6-methyladenine (m6A) is one of the most common RNA epigenetic modifications in all higher eukaryotes. Increasing evidence demonstrated that m6A-related proteins, acted as oncogenes or tumor suppressors, are abnormally expressed in the cell lines and tissues of non-small cell lung cancer (NSCLC). In addition, lung as the special immune organ contacts with the outer environments and thereby inevitably suffers from different types of microbial pathogen attack. Those microbial pathogens affect the development, progression, and clinical outcomes of NSCLC via altering host m6A modification to disrupt pulmonary immune homeostasis and increase the susceptibility; conversely, host cells modulate m6A modification to repress bacterial colonization. Therefore, m6A harbors the potential to be the novel biomarkers and targets for predicting poor prognosis and chemotherapy sensitivity of patients with lung cancer. In this paper, we provided an overview of the biological properties of m6A-modifying enzymes, and the mechanistic links among lung microbiota, m6A modification and NSCLC. Although the flood of novel m6A-related inhibitors represents many dramatic improvements in NSCLC therapy, their efficacy and toxicity in NSCLC are explored to address these pivotal gaps in the field.